Chemical Characterization and Antioxidant Potential of Athroisma proteiformis Essential Oil - Rasolohery, Claudine A.; Ralaibia, Boniface Erménegilde; Gotor, Alicia Ayerdi; Merlier, Franck; Benja, Rakotonirina; Rakotovao, Marcelle; Rhazi, Larbi (Natural Products Journal, The, 2017)
Objective: n the present study, the essential oil of Athroisma proteiformis was characterized for the first time. Method: GC-HRMS (Gas Chromatography-High Resolution Mass Spectrometry) was performed for qualitative and quantitative analysis of the phytochemicals present in the extract. Chemical analyses were conducted to evaluate the total phenols, total flavonoids and antioxidant activity of the extract. Results: Of the 130 peaks detected, 50 were studied and 30 compounds were clearly identified. The main components of the extract were p-cymen-8-ol, the major compound (13.37%), followed by caryophyllene oxide (12.02%), o-cymene (7.79%), humulene epoxide II (7.62%) and limonene (7.35%). The essential oil of Athroisma proteiformis exhibited a good antioxidant activity. The Athroisma extract IC50 values were lower than those of the antioxidant standards used in the FRAP and ABTS tests, ascorbic acid and BHT, and lower than glutathione in the OH radical reducing power test. On the contrary, in the DPPH test, IC50 was higher for A. proteiformis than for ascorbic acid or BHT. Conclusion: It can be concluded that the A. proteiformis plant can be used as a source of natural antioxidants but the consequences on human health should first be carefully studied due to the large number of compounds present in the oil.
Keywords: essential oil